Peer to peer mentoring: Outcomes of third-year midwifery students mentoring first-year students. Issue 3 (June 2017) - Hogan, Rosemarie; Fox, Deborah; Barratt-See, Georgina
Abstract: Problem: Undergraduate midwifery students commonly experience anxiety in relation to their first clinical placement. Background: A peer mentoring program for midwifery students was implemented in an urban Australian university. The participants were first-year mentee and third-year mentor students studying a three-year Bachelor degree in midwifery. The program offered peer support to first-year midwifery students who had little or no previous exposure to hospital clinical settings. Mentors received the opportunity to develop mentoring and leadership skills. Aim: The aim was to explore the benefits, if any, of a peer mentoring program for midwifery students. Methods: The peer mentoring program was implemented in 2012. Sixty-three peer mentors and 170 mentees participated over three academic years. Surveys were distributed at the end of each academic year. Quantitative survey data were analysed descriptively and qualitative survey data were analysed thematically using NVivo 10 software. Findings: Over 80% of mentors and mentees felt that the program helped mentees adjust to their midwifery clinical placement. At least 75% of mentors benefited, in developing their communication, mentoring and leadership skills. Three themes emerged from the qualitative data, including 'Receiving start-up advice'; 'Knowing she was there' and 'Wanting more face to face time'. Discussion: There is a paucity of literature on midwifery student peer mentoring. The findings of this program demonstrate the value of peer support for mentees and adds knowledge about the mentor experience for undergraduate midwifery students. Conclusion: The peer mentor program was of benefit to the majority of midwifery students.